Synthesis of 2-Amino-5-hydroxypyridine via Demethoxylation - Cheng, J.; Liu, C. (Asian Journal of Chemistry, 2016)
A convenient and efficient four-step synthesis of 2-amino-5-hydroxypyridine can be achieved by protective reaction of 2-amino-5-bromopyridine in the presence of 2,5-hexanedione to yield 5-bromo-2-(2,5-dimethyl-1H-pyrrol-1yl)pyridine, methoxylation with sodium methylate to give 5-methoxy-2-(2,5-dimethyl-1H-pyrrol-1yl)pyridine, deprotective reaction with hydroxylamine hydrochloride to produce 2-amino-5-methoxypyridine and demethylation with 95 % H2SO4 to afford the title compound in an overall yield of 45 %.